Working Hours and Top Management Appointments: Evidence from Linked Employer-Employee Data - Anders Frederiksen; Takao Kato; Nina Smith (Institute of Labor Economics (IZA), 2018)
By combining Danish registry data covering the population of Danish workers with the Danish Labor Force Survey (DLFS) which provides detailed data on working hours, we provide fresh evidence and insights on a potentially important role that career concerns/considerations play in accounting for the incidence of long working hours. First, we obtain new and robust evidence with external validity on a positive association between working hours and career success (measured by top management appointments). Second, we illuminate that the observed positive association between working hours and career success is consistent with three distinct theories: (i) human capital; (ii) rat race; and (iii) tournament. Third, guided by each theory, we go beyond a simple association between the quantity of working hours and career success, and explore what kinds of working hours are more beneficial for career advancement. Specifically we find: (i) for managers, working long hours will help them increase their odds of top management appointments in the same firm, while not in a different firm, while for non-managerial professionals and other workers, both internal and external hours will help them raise their odds of career success; (ii) the odds of top management appointments will rise significantly by becoming the longest working hour person among the peers; (iii) working nonstandard hours (evening/night) will be beneficial for career advancement; and (iv) workers with high desired hours will enjoy greater odds of top management appointments even after controlling for actual hours. We interpret each finding from the three theoretical perspectives.
Keywords: M5; 330; working hours; top management appointments; promotions; human capital; job assignment; rat race; adverse selection; tournament